Adaptation of Rice Varieties (Oryza sativa L.) in Paddy Fields Rain Feeding through The Use of Ameliorant in Lahat Regency - Rosita Rosita; Gusmiatun Gusmiatun; Neni Marlina (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice is a food crop commodity that serves as the staple food for the Indonesian population. This study examines the adaptation of various rice varieties with the addition of ameliorants on growth and yield in rainfed paddy fields. The research was conducted in Lahat District, Lahat Regency, from January to May 2024, utilizing a split-plot design with 12 treatment combinations, each replicated three times. The main plot treatments consisted of ameliorants, while the subplot treatments involved different rice varieties. The observed parameters included plant height (cm), number of tillers, number of productive tillers, panicle length (cm), flowering age (days after sowing), harvest age (days after sowing), total grains per panicle (grams), percentage of empty grains (%), 1000-grain weight (grams), and productivity (ton/ha). The results indicated that applying ameliorants, such as lime and solid organic fertilizer, yielded the most favorable outcomes for rice plant growth. Tabular analysis revealed that the Situ Bagendit variety exhibited the highest productivity compared to other varieties. Furthermore, the combination of ameliorants, specifically lime and organic fertilizer, along with the Situ Bagendit variety, achieved the highest paddy productivity at 5.13 tons per hectare.